Gamifikasi: Peranan dalam Proses Pembelajaran - Pambudi, Yudha Rello; Riski, Dwiko Febrama; Jannah, Nurul; Mawaddah, Nada (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The rapid and rapid development of technology and information has greatly influenced all fields, including the field of education, especially learning. According to a survey by the Indonesian Teacher Association, it is stated that 60% of teachers in Indonesia have inadequate skills or can be said to be lagging behind in the use of technology, this will have an impact on the quality of education in Indonesia. Teachers must be able to create a classroom atmosphere that is fun, dynamic and interesting so that students can follow the learning process well. In an effort to create a dynamic and interesting learning environment, the concept of gamification has emerged as a promising alternative. The method used in this research is literature review, literature review is a search and research of the literature by reading various books, journals and publications related to an issue or research topic. Gamification has a very important role in education and is very suitable to be applied to children (especially elementary school students) in the learning process because games are something that children like, not just adding game elements for the enjoyment of students, but will also influence the whole learning process. Starting from providing fun, motivating and active students.